Global Financial Stability Report, March 2002 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2002)
This March 2002 issue of the Global Financial Stability Report highlights that financial markets ended the year 2001 on a positive note. Equity markets recovered and rallied noticeably from their lows of late September. In bond markets, yield spreads of corporate and high-yielding bonds, particularly emerging market bonds, narrowed against the U.S. Treasury. At the same time, the U.S. Treasury yield curve steepened, and the U.S. dollar has strengthened. Financial markets thus anticipate, and have priced in, a recovery in economic activity and corporate earnings during 2002.